Colombian Andean thermal springs: reservoir of thermophilic anaerobic bacteria producing hydrolytic enzymes (2019)
Anaerobic cultivable microbial communities in thermal springs producing hydrolytic enzymes were studied. Thermal water samples from seven thermal springs located in the Andean volcanic belt, in the eastern and central mountain ranges of the Colombian Andes were used as inocula for the growth and isolation of thermophilic microorganisms using substrates such as starch, gelatin, xylan, cellulose, Tween 80, olive oil, peptone and casamino acids. These springs differed in temperature (50–70 °C) and pH (6.5–7.5). The predominant ion in eastern mountain range thermal springs was sulphate, whereas that in central mountain range springs was bicarbonate. A total of 40 anaerobic thermophilic bacterial strains that belonged to the genera Thermoanaerobacter, Caloramator, Anoxybacillus, Caloranaerobacter, Desulfomicrobium, Geotoga, Hydrogenophilus, Desulfacinum and Thermoanaerobacterium were isolated. To investigate the metabolic potential of these isolates, selected strains were analysed for enzymatic activities to identify strains than can produce hydrolytic enzymes. We demonstrated that these thermal springs contained diverse microbial populations of anaerobic thermophilic comprising different metabolic groups of bacteria including strains belonging to the genera Thermoanaerobacter, Caloramator, Anoxybacillus, Caloranaerobacter, Desulfomicrobium, Geotoga, Hydrogenophilus, Desulfacinum and Thermoanaerobacterium with amylases, proteases, lipases, esterases, xylanases and pectinases; therefore, the strains represent a promising source of enzymes with biotechnological potential. © 2019, Springer Japan KK, part of Springer Nature.